Trends in international investment agreements : an overview (UN New YorkUS, 1999)
Focuses on international agreements (in force or not yet in force) that directly concern and affect foreign direct investment, while also taking into account other aspects such as trends in national law, non-binding international instruments.
Keywords: INTERNATIONAL INVESTMENT